Analisis Penguasaan Konsep Siswa SMA pada Materi Fluida Statis melalui Pembelajaran PBL Berbantuan Google Sites - Ristanti Mulia Indraloka; Purbo Suwasono; Herlin Pujiarti (Jurnal Penelitian Pendidikan IPA, 2025)
The purpose of this study was to analyze the effectiveness of PBL assisted by Google Sites in improving students' mastery of static fluid concepts. The research used mixed method research, Sequential Explanatory design. The research subjects were students of SMAN 01 Candipuro class XI MIPA, consisting of 35 experimental class students and 35 control class students. Quantitative data obtained from pretest and posttest with multiple choice instrument questions. The results of the T test on the pretest (0.931) showed no difference in initial ability between classes, while the Mann-Whitney test on the posttest (0.000) showed a significant difference between the two classes. The effectiveness of PBL aided by Google Sites is shown by the N-Gain of the experimental class (0.77, high category) which is greater than the N-gain of the control class (0.39, medium category). Qualitative data obtained from interviews revealed that the features of Google Sites, the presentation of contextual problems through videos, images, articles, and the investigation stage helped students build their own concepts and overcome misconceptions. This finding shows that PBL assisted by Google Sites is effective in improving students' mastery of the concept of static fluid.